Estudo de sistemas lineares por parte com três zonas e aplicação na análise de um circuito elétrico envolvendo um memristor - Scarabello, Marluce da Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Em um artigo publicado em maio de 2008 na revista Nature [17], um grupo de pesquisadores da Hewllet-Packard Company (HP) anunciou a fabricação de um componente eletrônico chamado memristor, uma contração para “memory resistor”. A existência teórica dos memristores havia sido prevista em 1971, pelo Engenheiro da Universidade da Califórnia em Berkeley, Leon Chua, com base em propriedades de simetria de certos circuitos elétricos, porém até 2008 sua existência física não havia sido comprovada. Tal componente é considerado o quarto componente eletrônico fundamental, ao lado do resistor, do capacitor e do indutor, pois possui propriedades que não podem ser duplicadas por nenhuma combinação desses três outros componentes. A construção física do memristor atraiu grande interesse no mundo todo, devido ao grande potencial de aplicações deste componente. No presente trabalho fazemos um estudo das bifurcações que ocorrem em um sistema de equações diferenciais ordinárias, que serve como modelo matemático de um circuito elétrico formado pelos quatro elementos fundamentais: um memristor, um capacitor, um indutor e um resistor. O circuito estudado foi proposto por Itoh e Chua em [9]...

In the present work we make a bifurcation analysis of a system of ordinary differential equations, which serves as a mathematical model of an electric circuit formed by the four fundamental elements: one memristor, one capacitor, one inductor and one resistor. The studied circuit was proposed by Itoh and Chua in [9] and was constructed based on the well-known Chua's oscillators. The studied model is given by a discontinuous piecewise-linear system, defined on three zones in R 3, determined by the following inequalities: |z|<1 (called central zone) and |z|>1 (called external zones). The z-axis is composed by equilibrium points of the system. The local normal stability of these equilibira in each zone is analyzed. We show that, due to the existence of this line of equilibria, the phase space R 3 is foliated by invariant planes transversal to the z-axis and parallel to each other, in each zone. The solutions of the system are contained in a combination of three of these invariant planes: one of them in the central zone and the other two in the external zones. We also show that the system may present nonlinear oscillations due to the existence of periodic orbits passing through two of the three zones or passing by three zones. The analysis developed here has analytical and numerical parts. The analytical part was developed based on the study of planar piecewise-linear systems with three zones presented by Freire et al. in [5]... (Complete abstract click electronic access below)
Keywords: Computação - Matematica; Sistemas lineares; Piecewise linear systems; Memristor